Traumatic events and posttraumatic stress symptoms among adolescents in Ibadan (2011)
Little empirical data exist on the rates of exposure to traumatic events and its sequelae especially in adolescents. This study was designed to determine the lifetime prevalence of exposure to traumatic events and posttraumatic stress symptoms among adolescents in Ibadan, Nigeria. A sample of 786 boys and girls from 10 senior secondary schools located within Ibadan were interviewed using an adapted version of the Schedule for Affective Disorders and Schizophrenia (KSADS) to ascertain the prevalence of exposure to traumatic events and posttraumatic stress symptoms. Irrespective of gender, more than 40% reported lifetime exposure to at least one traumatic event. Commonly reported events were: receiving news of sudden injury, death or illness in a close family member or friend, being a victim or witness to a violent crime and physical abuse. About 2.4% of the sample met diagnostic criteria for posttraumatic stress disorder (PTSD). Female sex, exposure to more than one traumatic event, and sexual abuse were associated with increased risk for PTSD. The results of this study highlights the substantial risk for experiencing serious traumatic events by adolescents within the community, and a need for professionals involved in the care of adolescents to be more vigilant in screening for trauma related distress.